The Influence of Regional Asset Management and Internal Control Systems on the Quality of Financial Reporting in the Bandung City Education Department - Muhlisoh, Fitria ZamZam; Kurhayadi, Kurhayadi; Sucipto, Bambang (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
This research aims to find out whether regional asset management and the internal control system influence the quality of financial reports at the Bandung City Education Office. The independent variables are regional asset management and the internal control system, as well as the dependent variable, namely the quality of financial reports. This type of research is included in quantitative research, while the research methods used are descriptive and verification methods. The population in this research is employees in education units at the Bandung City Education Office, totaling 349 units. The sampling technique is probability sampling using simple random sampling, while to calculate the number of samples using the Slovin formula with a significance level of 10%, this is due to limited research permits granted by the Bandung City Education Office, so the total sample is 78 employees in education units at the Bandung City Education Office. The data analysis used in this research is multiple linear regression analysis using SPSS software. Partial and simultaneous research results show that regional asset management and the internal control system influence the quality of financial reports at the Bandung City Education Office. Apart from that, regional asset management and internal control systems has an influence on the quality of financial reports by 65.4%.